Quenching of the [ny]=32 neutron shell closure studied via precision mass measurements of neutron-rich vanadium isotopes - Reiter, Moritz Pascal; Bollig, Julian (Physical review, 2018)
We performed the first direct mass measurements of neutron-rich vanadium 52-55V isotopes passing the N=32 neutron shell closure with TRIUMF's Ion Trap for Atomic and Nuclear science. The new direct measurements confirm all previous indirect results. Through a reduced uncertainty of the mass of 55V we confirm the quenching of the N=32 neutron shell closure in vanadium. We discuss the evolution of the N=32 neutron shell closure between K and Cr and show similar signatures in the half-life surface when studied along the isotopic chains.